Survival analysis of pneumoconiosis patients in Jiangsu Province from 1960 to 2024 - Wang, Ning; Chu, Xinlei; Zhou, Lang; Zhao, Yuan; Gao, Qianqian; Gao, Yue; Zhou, Peng; Han, Lei (Frontiers in Public Health, 2025)
IntroductionPneumoconiosis is recognized as a major occupational health burden worldwide, especially in developing countries where industrial dust exposure is prevalent. This study aims to provide evidence for the development of prevention and control strategies and the strengthening of patient support systems.MethodsData for this study were sourced from the Jiangsu Province Pneumoconiosis Follow-up Online Reporting System. Survival analysis was performed employing life tables and the Kaplan–Meier method. The Cox proportional hazards regression models were deployed to identify factors influencing pneumoconiosis patients’ survival time.ResultsA total of 18,064 patients were diagnosed with pneumoconiosis in Jiangsu Province between 1960 and 2024. Life table analysis revealed an overall cumulative survival rate of 40%. Both mortality and hazard ratios increased with advancing age. Patients with Stage III pneumoconiosis had a significantly lower survival rate compared with those in stages I and II (p < 0.05). The results showed that gender, stage at first diagnosis, age at first diagnosis, and disease progression were significant factors influencing survival time.ConclusionOur findings highlight the importance of strengthening prevention and control measures targeting high-risk populations and key industries. Strategies should focus on early detection, timely diagnosis, and active intervention.